Effects of distillers grains on growth performance in nursery and finishing pigs - B W Senne; P S Sorrell; I H Kim; S L Traylor; Robert H Hines; Joe D Hancock; Keith C Behnke (Kansas Agricultural Experiment Station Research Reports, 1995)
Rate and efficiency of gain were not affected by adding as much as 20% distillers dried grains in isocaloric diets for nursery pigs or 30% in isocaloric diets for finishing pigs. These results demonstrate that the previously suggested maximums of 5% distillers dried grains in nursery diets and 10% distillers dried grains in finishing diets are too conservative. Finally, because the 20% (nursery) and 30% (finishing) treatments were the greatest concentrations used in our experiments, additional growth assays are needed to determine the maximum limits for distillers dried grains in diets for pigs.; Swine Day, Manhattan, KS, November 16, 1995
Keywords: Swine day; 1995; Kansas Agricultural Experiment Station contribution; no. 96-140-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 746; Swine; Distillers grains; Nursery; Finishing; Sorghum